Best Paper Selection (Yearbook of Medical Informatics, 2021)
Le DH. UFO: A tool for unifying biomedical ontology-based semantic similarity calculation, enrichment analysis and visualization. https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0235670Robinson PN, Ravanmehr V, Jacobsen JOB, Danis D, Zhang XA, Carmody LC, Gargano MA, Thaxton CL, Core UNCB, Karlebach G, Reese J, Holtgrewe M, Kohler S, McMurry JA, Haendel MA, Smedley D. Interpretable Clinical Genomics with a Likelihood Ratio Paradigm. https://www.cell.com/ajhg/fulltext/S0002-9297(20)30230-5Slater LT, Gkoutos GV, Hoehndorf R. Towards semantic interoperability: finding and repairing hidden contradictions in biomedical ontologies. https://bmcmedinformdecismak.biomedcentral.com/articles/10.1186/s12911-020-01336-2Zheng F, Shi J, Yang Y, Zheng WJ, Cui L. A transformation-based method for auditing the IS-A hierarchy of biomedical terminologies in the Unified Medical Language System. https://pubmed.ncbi.nlm.nih.gov/32918476/